2011
DOI: 10.1104/pp.111.177501
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Mitochondria-Localized Pentatricopeptide Repeat Protein PGN Functions in Defense against Necrotrophic Fungi and Abiotic Stress Tolerance      

Abstract: Pentatricopeptide repeat (PPR) proteins (PPRPs) are encoded by a large gene family in Arabidopsis (Arabidopsis thaliana), and their functions are largely unknown. The few studied PPRPs are implicated in different developmental processes through their function in RNA metabolism and posttranscriptional regulation in plant organelles. Here, we studied the functions of Arabidopsis PENTATRICOPEPTIDE REPEAT PROTEIN FOR GERMINATION ON NaCl (PGN) in plant defense and abiotic stress responses. Inactivation of PGN resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(131 citation statements)
references
References 91 publications
2
127
1
1
Order By: Relevance
“…Evidence for an interplay between ABA and mitochondria via mtROS has been found in lines with different sensitivity to ABA (Laluk et al, 2011; Collectively, these reports show that the underlying causes of increased ABA sensitivity in a range of mutants are mitochondrial defects. In some of these mutants, increases in ROS were reported, while others report decrease, using a variety of different detection methods.…”
Section: Mtros and Plant Hormone Signalingmentioning
confidence: 71%
“…Evidence for an interplay between ABA and mitochondria via mtROS has been found in lines with different sensitivity to ABA (Laluk et al, 2011; Collectively, these reports show that the underlying causes of increased ABA sensitivity in a range of mutants are mitochondrial defects. In some of these mutants, increases in ROS were reported, while others report decrease, using a variety of different detection methods.…”
Section: Mtros and Plant Hormone Signalingmentioning
confidence: 71%
“…Transcriptomics enables us to identify potential candidate genes functioning in plant defense, whereas mutant lines with knockout and/or overexpression traits allow us to elucidate their function in the defense response. Botrytis-induced kinase 1 ( BIK1 ), responsive to dehydration 20 ( RD20 ), pentatricopeptide repeat protein for germination on NaCl ( PGN ), and expansin-like A2 ( EXLA2 ) were identified as B. cinerea -responsive genes, and their mutants exhibited altered susceptibility to necrotrophic pathogens (Veronese et al, 2006; Laluk et al, 2011; AbuQamar et al, 2013; AbuQamar, 2014; Sham et al, 2015). Moreover, the Mediator 18 ( MED18 ), identified using RNAseq, was shown to modulate plant immunity and responses to hormones (Lai et al, 2014).…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Generally it is accepted that the reactions of plants to necrotrophic pathogens are associated with jasmonic acid (JA) and/or ethylene (ET) signal transduction pathways, while biotrophic pathogens induce salicylic acid (SA) pathway (Glazebrook 2005). In addition, the recent studies have demonstrated that abscisic acid (ABA) is a regulator of plant defence against necrotrophs (Laluk et al 2011). Adie et al (2007) observed that ABA-impaired mutants simultaneously showed high susceptibility to Pythium irregulare and Alternaria brassicicola and increased resistance to Botrytis cinerea.…”
Section: Introductionmentioning
confidence: 99%